Antitrust in a time of populism - Shapiro, Carl (International journal of industrial organization, 2018)
•Moderate increases in market concentration have taken place in many sectors in the United States over the past 20 to 30 years, but these increases do not indicate a systematic decline in competition in the United States.•Corporate profits have grown sharply as a share of GDP in the United States over the past twenty years, most likely due to the efficiency of some large firms and to growing barriers to entry in some industries.•Economic evidence supports a move toward moderately more vigorous merger enforcement in the United States.•Close antitrust scrutiny is appropriate for today’s largest and most powerful firms, including those in the high-tech sector.•Populist calls to abandon the consumer welfare standard in antitrust are not supported by the evidence, and no better alternative has been offered. This article discusses how to move antitrust enforcement forward in a constructive manner during a time of widespread and growing concern over the political and economic power of large corporations in the United States. Three themes are emphasized. First, a body of economic evidence supports more vigorous merger enforcement in the United States. Tighter merger control can be achieved by utilizing the existing legal presumption against highly concentrating mergers. Second, close antitrust scrutiny is appropriate for today's largest and most powerful firms, including those in the tech sector. Proper antitrust enforcement regarding unilateral conduct by dominant firms should continue to focus on identifying specific conduct that harms customers or disrupts the competitive process. Third, while antitrust enforcement has a vital role to play in keeping markets competitive, antitrust law and antitrust institutions are ill suited to directly address concerns associated with the political power of large corporations or other public policy goals such as income inequality or job creation.